Hybrid Test on a Simply Supported Bridge With High-Damping Rubber Bearings - Yang, Chengyu; Cai, Xuesong; Lai, Ziqin; Yuan, Yong (Frontiers in Built Environment, 2020)
High-damping rubber (HDR) bearings are widely used in girder bridges. To make a full-scale or large-scale test to the whole bridge is still unpractical in laboratory. Sub-structure hybrid simulation techniques could conquer the difficulties brought by the scale issues to some extent. In this study, hybrid simulations techniques are conducted for a simply-supported bridge with HDR bearings. The continuous exchange of the data between the numerical model and the physical specimen is conducted through the software framework, OpenFresco. An experimental bearing element is introduced to present the HDR bearings, while the remainder of the structure is modeled with beam-column elements for numerical analysis. This hybrid simulation results match well the analytical results under the designated earthquake excitation. Therefore, this introduced technique is proven to reproduce the seismic performance of a simply-supported bridge with HDR bearings. In the end, a series of dynamic hybrid simulations of the simply-supported bridge is performed, which provides useful insights into the selection of HDR bearings. The mechanical properties of such HDR bearings under the earthquake excitations are analyzed and discussed.